Production and characterization of a thermostable and organic solvent tolerant lipase by isolated fungi using palm kernel cake - Riyadi, Fatimah Azizah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
This research sought to explore the potential of palm kernel cake (PKC) to act as an oil and lipid rich environment for fungal growth, as well as a substrate to produce thermostable and organic solvent tolerant lipase through solid-state bioconversion. Four thermal and solvent tolerant fungi have successfully isolated with lipase producing capabilities. Among the four isolates, PKC12B2 displayed highest lipase activities and selected as the potential strain for the subsequent lipase production. Statistical analysis in the form of definitive screening design (DSD), one-factor-at-a-time (OFAT) and faced centered central composite design (FCCCD) were used to obtain optimum solid-state fermentation (SSF) medium compositions and process conditions for maximum lipase production. Through DSD as the initial screening step, peptone, (NH4)2SO4, olive oil, inoculum size, pH and moisture content were found to have the most significant contribution toward lipase production in PKC-based medium. Meanwhile, the classical OFAT studies revealed that olive oil, inoculum size and pH were associated with the high lipase production. Based on this, optimization of these three factors was carried out using FCCCD to develop a second-order regression model and a successful improvement in the lipase production was achieved. The optimum lipase production was 58.63 U/gds, which was attained within 72 hours fermentation time at 45 oC under the optimum conditions of 2 %v/w inoculum size, 2 %v/w olive oil, 0.6 %w/w peptone, 2 % ethanol as well as 70.0 % initial moisture content at pH of 10.0. PKC12B2 lipase was also subjected for biochemical characterizations in terms of activity and stability towards different pH, temperature, organic solvents and surfactants. The optimum pH for the enzyme was at pH 9.0 with good stability between pH 8.0 and 10.0, indicating its alkaline nature. The enzyme produced was also considered thermostable, possessing optimum temperature at 45 oC and thermal stability in the temperature range between 45 and 55 oC. In addition, the produced lipase exhibit satisfactory stability towards broad range of organic solvents, including polar and non-polar solvents (glycerol, isopropanol, methanol, ethanol, acetone, n-octanol, cyclohexane, and heptane). PKC12B2 lipase also exhibited stimulatory effects towards low surfactants Tween 80, and Triton X-100 concentration (0.1 %), but higher concentration (1 %) of Tween-80 led to inhibitory effect. Kinetic studies of the produced enzyme were also performed. Linearized Michaelis-Menten model in the form of Lineweaver-Burk (R2=0.995) and Hanes-Woolf (R2=0.996) models could successfully be used to model the enzyme kinetics, in which the former generated Km and Vmax of 1.965 mM and 4.51mM/min respectively, while the latter generated Km and Vmax of 1.295mM and 3.389mM/min, respectively. All of these studies proved new enzyme attributes possessed by PKC12B2 lipase, which is of a great potential in biotechnology applications, such as for detergent formulations, biodiesel production and organic synthesis industries.